Optimization of bioenergy technologies - Tashyriev, Oleksandr; Hovorukha, Vira; Havryliuk, Olesia; Gladka, Galyna; Bida, Iryna (Problems of Environmental Biotechnology, 2024)
The goal of our research was to develop new theoretical approaches to create the latest universal environmental biotechnologies that not only allow for the rapid and efficient disposal of a wide range of environmentally hazardous wastes, but also for the production of useful products from them.